Simultaneous Spectrophotometric Assay for Estimation of Norfloxacin and Metronidazole in Tablets - Basak, S.; Mandal, Sanchita; Chattopadhyay, Moitreyee (Asian Journal of Chemistry, 2010)
The present work deals with the simple, accurate, precise and economical method for the simultaneous estimation of norfloxacin and metronidazole in tablet dosage form by Vierodt's UV spectrophotometric method. The absorption maxima (lmax) of norfloxacin and metronidazole in 0.1 N HCl were found to be 278.0 and 277.5 nm respectively. Since the lmax values of the chosen drugs were found to be significantly close, 278 nm was undertaken as a measuring wavelength for the present study. The drugs of combination also shows significant absorption in the wavelength 320 nm which was chosen as the second wavelength for the experiment. Both of the drugs followed Beer's law in the concentration range 1-10 and 5-25 μg/mL, respectively. The A1 % values for norfloxacin and metronidazole in the wavelength 278 nm and 320 nm were estimated to be 1273 and 320; 346 and 51, respectively.